Analysis of differential neonatal lethality in cystathionine β‐synthase deficient mouse models using metabolic profiling. Issue 6 (4th May 2021) - Gupta, Sapna; Wang, Liqun; Slifker, Michael J.; Cai, Kathy Q.; Maclean, Kenneth N.; Wasek, Brandi; Bottiglieri, Teodoro; Kruger, Warren D.
Abstract: Cystathionine beta‐synthase (CBS) is a key enzyme of the trans‐sulfuration pathway that converts homocysteine to cystathionine. Loss of CBS activity due to mutation results in CBS deficiency, an inborn error of metabolism characterized by extreme elevation of plasma total homocysteine (tHcy). C57BL6 mice containing either a homozygous null mutation in the cystathionine β‐synthase ( Cbs −/− ) gene or an inactive human CBS protein ( Tg‐G307S Cbs −/− ) are born in mendelian numbers, but the vast majority die between 18 and 21 days of age due to liver failure. However, adult Cbs null mice that express a hypomorphic allele of human CBS as a transgene ( Tg‐I278T Cbs −/− ) show almost no neonatal lethality despite having serum tHcy levels similar to mice with no CBS activity. Here, we characterize liver and serum metabolites in neonatal Cbs +/−, Tg‐G307S Cbs −/−, and Tg‐I278T Cbs −/− mice at 6, 10, and 17 days of age to understand this difference. In serum, we observe similar elevations in tHcy in both Tg‐G307S Cbs −/− and Tg‐I278T Cbs −/− compared to control animals, but methionine is much more severely elevated in Tg‐G307S Cbs −/− mice. Large scale metabolomic analysis of liver tissue confirms that both methionine and methionine‐sulfoxide are significantly more elevated in Tg‐G307S Cbs −/− animals, along with significant differences in several other metabolites including hexoses, amino acids, other amines, lipids, and carboxylic acids. Our data are consistent with a model that the neonatal lethality observed in CBS ‐null mice is driven by excess methionine resulting in increased stress on a variety of related pathways including the urea cycle, TCA cycle, gluconeogenesis, and phosphatidylcholine biosynthesis.